Soil Degradation Evidence Following a Wildfire in Arequipa’s Andean Region, Peru - Coaguila, Lunsden; Mataix-Solera, Jorge; Nina, Sonia; García-Carmona, Minerva; Salazar, Elizabeth T. (Spanish Journal of Soil Science, 2025)
Fire is a natural ecological force, but its effects vary significantly depending on the ecosystem. While fire-adapted ecosystems, such as Mediterranean woodlands, recover quickly, non-fire adapted regions like the Peruvian Andes are highly vulnerable to soil degradation, especially with increasing wildfire frequency and intensity due to climate change. The study investigates the effects of a 2018 wildfire in the Pichu Pichu volcano mountain area, a shrubland ecosystem at 3,700 m a.s.l. The arid conditions and unique soil characteristics, such as the Torripsamment soil on volcaniclastic sandstones, make the area particularly vulnerable to fire-induced degradation. Soils were evaluated three and 4 years after the fire event under two key dominant plant species in the ecosystem: Berberis lutea and Parastrephia quadrangularis. The results show that the combined fire and post-fire erosion processes significantly impacted soil properties, leading to a loss of soil organic carbon (SOC), increased bulk density (BD), loss of soil structure and, in the second sampling, a strong reduction in clay content attributable to weak aggregation and erosive processes. Soils under Berberis exhibited greater SOC losses, likely due to its larger biomass that intensified the combustion effects. The decrease in SOC resulted in soil compaction. Water repellency (WR), a natural feature in these soils due to the high sand content, remained largely unaffected by the fire. However, the persistence of WR may hinder water infiltration, increasing surface runoff and erosion, especially in the absence of vegetation post-fire. The findings highlight the fragility of these Andean soils to fire events, contrasting with the resilience that Mediterranean ecosystems often display. This lack of recovery underscores the need for improved wildfire prevention and post-fire soil management strategies, particularly as climate change further exacerbates the risks of soil degradation due to reduced water availability and more frequent fires in these fragile arid ecosystems.